Caring for Loved Ones with Heart Disease - Shah, J (Rowman & Littlefield Publishers, 2022)
Guides caregivers of those with heart disease through the process of supporting their loved one without sacrificing their own personal needs and wellbeing. Over 30 million people in the US suffer from heart disease and it is universally feared as the most common cause of death. Through the various stages of heart disease, patients need increasing care from their friends, family members, or other caregivers. Caring for Loved Ones with Heart Disease helps caregivers get appropriately involved in the care of their loved one’s heart disease management and treatment while maintaining their own physical, emotional, and spiritual wellbeing. Offering accessible information about heart diseases, treatments, common problems, the challenges of caregiving, and more, this work fills the increasing need among caregivers to understand everything their loved one will face from the doctor’s office to operating room to home care. Importantly, however, Jignesh Shah does not overlook the needs of the caregiver, providing tips and tools for balancing the complexities of advocacy and hand-on care with the physical, mental, emotional, and social needs of the caregiver. Shah teaches readers about various resources to help maintain a balance between performing these critical functions and tending to their own needs. Any friend or family member assisting in the care of a loved one will find the guidance offered throughout this book indispensible.